STRATEGI STP PRODUK SELAI NENAS DENGAN PEMANIS STEVIA: STUDI PENERIMAAN PASAR LOKAL SEHAT DI BINTAN : STRATEGI STP PRODUK SELAI NENAS DENGAN PEMANIS STEVIA: STUDI PENERIMAAN PASAR LOKAL SEHAT DI BINTAN - Hetty Yulianti Sihite; Aprilia Nurcahyaning Rahayu; Mashudi - (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2025)
This research is driven by the increasing public awareness of healthy lifestyles, particularly in choosing food and beverage products that are low in calories and free from added sugars. One of the most widely used natural sweeteners as a sugar substitute is stevia. The purpose of this study is to identify consumer preferences toward pineapple jam products made with stevia and to formulate marketing strategies based on segmentation, targeting, and positioning (STP) approaches. The research employed a descriptive quantitative method by distributing questionnaires to 100 respondents who are residents of Bintan Regency. The results indicate that the majority of respondents are within the productive age group and demonstrate a high level of awareness regarding healthy food consumption. A total of 78% of respondents expressed a preference for products using natural sweeteners, while 81% perceived that the stevia-based pineapple jam is healthier than regular jam. The segmentation strategy focuses on consumers aged 25–45 years with a healthy lifestyle, the targeting is directed at women as primary decision-makers in household consumption, and the product is positioned as a natural and healthy jam without compromising on taste. The conclusion of this study suggests that pineapple jam made with stevia has promising market potential, especially among health-conscious consumers. Recommendations for producers include enhancing consumer education and strengthening packaging and distribution to reach a broader market.